Human longevity : omega-3 fatty acids, bioenergetics, molecular biology, and evolution - Valentine, R. C. (Raymond Carlyle), 1936-; Valentine, David L. (CRC Press, 2014)
More than 7 billion people inhabit the earth and all of them are subject to aging. This book is aimed at persons interested in a molecular explanation of how our cells age. Human Longevity: Omega-3 Fatty Acids, Bioenergetics, Molecular Biology, and Evolution is built on the proposition that we age as our mitochondria age. It suggests a revised version of Harman's famous hypothesis featuring mitochondrial oxidative and energy stresses as the root causes of aging. Human cells are protected from the ravages of aging by a battery of defensive systems including some novel mechanisms against membran.